Computer-Assisted Training in the Conditions of the Emergence of Devices - Beteringhe, Adrian; Stanciu, Lidia; Stanciu, Filip (Didactica Danubiensis, 2022)
The pandemic has created in the educational community not only a discomfort in terms of the health of each member, but also a chaotic use of all IT devices. Under these conditions, the usefulness of computer-assisted training in the curriculum of primary, secondary, high school and higher education is analyzed.